Urban Slum Morphology and Socio-economic Analogies: A Case Study of Kibera Slum, Nairobi, Kenya. (May 2018) - Mukeku, Joseph
Narratives around slums tend to amplify their negative attributes, often based on a sensorial assessment of their environment. This article talks about a study carried out in Kibera, the second largest slum in Africa located in Nairobi, Kenya, which examines how slums are morphologically constituted with respect to their socio-economic settings. The study stems from the author's several years of work as a community design architect on slum upgrading projects, many of which were of a participatory nature. Given that slums exist outside of formal planning and lack documented development records, a basic approach to studying slums was adopted. This article uses analogies to expound on the link between the spatial-temporal formation of the slum and the socio-economic activities and practices of its residents. It goes on to show the crucial need for slum upgrading programmes to pay attention to this strong yet hidden interrelationship in order to meet the needs of the beneficiaries in a sustainable manner.